Dakwah Kultural di Pesisir Mandailing Natal: Upaya Menjaga Tradisi di Tengah Arus Modernisasi - Nurjamil, Rifki; Hakim, Lukman (Mafa Press, 2026)
This study explores how cultural da’wah is practiced within the coastal communities of Natal Subdistrict, Mandailing Natal Regency, North Sumatra, and how it contributes to preserving local traditions amid the tide of modernization. The main purpose of this research is to understand the forms and strategies of cultural da’wah developed in coastal societies and to examine its influence on the social and religious life of local people. This research employs a qualitative descriptive approach using field study methods, including interviews, observations, and documentation involving religious leaders, traditional figures, and fishing communities. The findings reveal that cultural da’wah in coastal areas is carried out through persuasive and adaptive approaches that integrate local culture—such as religious activities based on local traditions and the use of regional languages in delivering religious messages. This approach has proven effective in strengthening religious understanding while preserving the community’s cultural values, showing that da’wah serves not only as a means of spreading Islamic teachings but also as a medium for maintaining social identity in the face of modernization.